The making of electronic modules on alternative fuels material based on green chemistry - Afifah, A; Subarkah, C; Aisyah, R (Journal of physics. Conference series, 2019)
This research was conducted to produce teaching materials in the form of e-modules on alternative fuels based on green chemistry fuel material. The presentation of material and visualization that used in this e-module based on green chemistry includes the losses caused by the use of fuel oil and the solutions offered to overcome them by the presence of alternative fuels based on green chemistry. This research uses the Design Based Research method with the ADDIE model. The e-module is tested for its feasibility. The results of the feasibility test show 94-100% of the respondents agreed to all the criteria in the e-module. These results indicate that the green chemistry-based alternative fuel e-module that has been made is feasible to use. This research is useful to increase student awareness about the importance of protecting environment through chemistry learning process.